The Enigma behind Pituitary and Sella Turcica - Umarevathi Gopalakrishnan; Lodd Mahendra; Sumanth Rangarajan; Ramasamy Madasamy; Mohammad Ibrahim (Hindawi Limited, 2015)
The pituitary gland's role as a functional matrix for sella turcica has not been suggested in orthodontic literature. This paper is an attempt to correlate the role of pituitary gland in the development of sella turcica. A case report of dwarfism associated with hypopituitarism is presented to highlight the above hypothesis.